Specialized Biopsychosocial Care in Inpatient Somatic Medicine Units—A Pilot Study - Köbler, Paul; Krauss-Köstler, Eva K.; Stein, Barbara; Ficker, Joachim H.; Wilhelm, Martin; Dechêne, Alexander; Waller, Christiane (Frontiers in Public Health, 2022)
Introduction Specialized biopsychosocial care concepts are necessary to overcome the dualism between physical and psychosocial treatment in acute care hospitals. For patients with complex and chronic comorbid physical and mental health problems, neither standardized psychiatric/psychosomatic nor somatic care units alone are appropriate to their needs. The “Nuremberg Integrated Psychosomatic Acute Unit” (NIPA) has been developed to integrate treatment of both, psychosocial and physical impairments, in an acute somatic care setting. Method NIPA has been established in inpatient internal medical wards for respiratory medicine, oncology and gastroenterology. One to two patients per ward are regularly enrolled in the NIPA treatment while remaining in the same inpatient bed after completion of the somatic care. In a naturalistic study design, we evaluated treatment effects by assessment of symptom load at admission and at discharge using the Patient Health Questionnaire (PHQ) and the Generalized Anxiety Disorder Scale-7 (GAD-7). Furthermore, we assessed the severity of morbidity using diagnosis data during treatment. At discharge, we measured satisfaction with treatment through the Patient Satisfaction Questionnaire (ZUF-8). Results Data from 41 NIPA patients were analyzed (18–87 years, 76% female). Seventy-eight percent suffered from at least moderate depression and 49% from anxiety disorders. Other diagnoses were somatoform pain disorder, somatoform autonomic dysfunction, eating disorder and posttraumatic stress disorder. Hypertension, chronic lung diseases and musculoskeletal disorders as well as chronic oncological and cardiac diseases were the most common somatic comorbidities. Treatment resulted in a significant reduction of depressive mood (admission: M = 10.9, SD = 6.1, discharge: M = 7.6, SD = 5.3, d = 0.58, p = 0.001), anxiety (admission: M = 10.6, SD = 4.9, discharge: M = 7.3, SD = 4.1, d = 0.65, p< 0.001) and stress (admission: M = 6.0, SD = 3.6, discharge: M = 4.1, SD = 2.5, d = 0.70, p< 0.001). Somatic symptom burden was reduced by NIPA treatment (admission: M = 10.9, SD = 5.8, discharge: M = 9.6, SD = 5.5, d = 0.30), albeit not statistically significant (p = 0.073) ZUF-8 revealed that 89% reported large or full satisfaction and 11% partial dissatisfaction with treatment. Discussion NIPA acute care is bridging the gap for patients in need of psychosocial treatment with complex somatic comorbidity. Further long-term evaluation will show whether psychosocial NIPA care is able to reduce the course of physical illness and hospital costs by preventing hospitalization and short-term inpatient re-admissions.